Testosterone therapy may reduce prostate cancer risk due to testosterone deficiency at a young age via stabilizing serum testosterone levels. (2nd April 2020) - Zhang, Xiao; Zhong, Yan; Saad, Farid; Haider, Karim Sultan; Haider, Ahmad; Clendenin, Angela G.; Xu, Xiaohui
Abstract: Objectives: To investigate whether testosterone replacement therapy (TRT) reduces prostate cancer (PCa) risk via stabilizing serum testosterone (T) levels beyond simply elevating serum T levels and whether TRT reduces PCa risk due to low serum T levels at a young age. Methods: We analyzed data of 776 hypogonadal men from a urology center in Bremerhaven, Germany through 2004–2016 to investigate whether the TRT group has more stable T levels and whether TRT can reduce the risk of PCa due to low serum T levels at an early age. We derived an index, Maximum Decline of T Relative to Baseline (MDRB), to describe the magnitude of T declines and variations over time. Results: We found the TRT group has more stable serum T levels (e.g. smaller drop-offs) during the follow-up period as compared to the non-TRT group, and the mean of MDRB is significantly higher in the untreated group (1.553 nmol/L VS 0.013 nmol/L; p -value < .001). TRT significantly reduces the risk of PCa associated with T deficiency at a young age ( p -value = .00087). Conclusions: TRT may reduce PCa risk via maintaining serum T levels within individual's normal range; T surveillance may be needed for males who have low serum T levels at a young age to monitor abnormal variations of T levels and ensure timely treatment when necessary to reduce PCa risk.